Madrasah Head Strategies In Implementing The Independent Curriculum Atman Batu Bara - Siregar, Ridho Khairul Azizi; Mesiono; Makmur Syukri (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the madrasah head's strategy in implementing the Merdeka Curriculum at MAN Batu Bara, focusing on the understanding of the madrasah head and teachers, strategic implementation steps, and competence in using technology. The research method used is qualitative with a Phenomenological approach. Data were collected through in-depth interviews and observations of the madrasah head, teachers, students and related documentation. The results showed that the level of understanding of madrasah principals and teachers about the concept and objectives of Merdeka Curriculum is relatively high, which is reflected in the implementation of daily learning practices. Strategic steps such as the formation of a curriculum development team, intensive training, and adjusting the madrasah's vision and mission are key to successful implementation. In addition, the competence in using technology by madrasah principals and teachers has supported the effectiveness of teaching based on the Merdeka Curriculum, although there are challenges in adopting technology by a small number of teachers.